Hairy Root Transformation Using Agrobacterium rhizogenes as a Tool for Exploring Cell Type-Specific Gene Expression and Function Using Tomato as a Model. Issue 2 (27th May 2014) - Ron, Mily; Kajala, Kaisa; Pauluzzi, Germain; Wang, Dongxue; Reynoso, Mauricio A.; Zumstein, Kristina; Garcha, Jasmine; Winte, Sonja; Masson, Helen; Inagaki, Soichi; Federici, Fernán; Sinha, Neelima; et al.
Abstract : Testing tomato gene expression with tagged nuclei and ribosomes and CRISPR/Cas9 genome editing shows conservation of SHORT-ROOT gene function . Abstract: Agrobacterium rhizogenes (or Rhizobium rhizogenes ) is able to transform plant genomes and induce the production of hairy roots. We describe the use of A. rhizogenes in tomato ( Solanum spp.) to rapidly assess gene expression and function. Gene expression of reporters is indistinguishable in plants transformed by Agrobacterium tumefaciens as compared with A. rhizogenes . A root cell type- and tissue-specific promoter resource has been generated for domesticated and wild tomato ( Solanum lycopersicum and Solanum pennellii, respectively) using these approaches. Imaging of tomato roots using A. rhizogenes coupled with laser scanning confocal microscopy is facilitated by the use of a membrane-tagged protein fused to a red fluorescent protein marker present in binary vectors. Tomato-optimized isolation of nuclei tagged in specific cell types and translating ribosome affinity purification binary vectors were generated and used to monitor associated messenger RNA abundance or chromatin modification. Finally, transcriptional reporters, translational reporters, and clustered regularly interspaced short palindromic repeats-associated nuclease9 genome editing demonstrate that SHORT-ROOT and SCARECROW gene function is conserved between Arabidopsis ( Arabidopsis thaliana ) and tomato.